An assessment of managerial knowledge, skills and attitudes required for implementing performance management system for organisational performance at Newcastle Municipality - Bhengu, Muzomuhle (Stellenbosch : Stellenbosch University, 2015)
Thesis (MPA)--Stellenbosch University, 2015.